Truncated Cauchy Power Odd Fréchet-G Family of Distributions: Theory and Applications. (27th October 2021) - Shrahili, M.; Elbatal, I.
Abstract : The truncated Cauchy power odd Fréchet-G family of distributions is presented in this article. This family's unique models are launched. Statistical properties of the new family are proposed, such as density function expansion, moments, incomplete moments, mean deviation, Bonferroni and Lorenz curves, and entropy. We investigate the maximum likelihood method for predicting model parameters of the new family. Two real-world datasets are used to show the importance and flexibility of the new family by using the truncated Cauchy power odd Fréchet exponential model as example of the family and compare it with some known models, and this model proves the importance and the flexibility for the new family.